Pelatihan Digital Marketing sebagai Optimasi Media Sosial Instagram Artenspace - Cendekia, Dhara Alim; Hermanto, Yon Ade Lose; Pahlevi, Andreas Syah; Firmansyah, Novian Wahyu (Indonesian Journal for Social Responsibility, 2025)
Artenspace is a community-based co-working space that features a gallery, meeting room, and programs aimed at helping artists showcase their work to the general public. Despite Artenspace's programs being supported by adequate facilities, the advantages of Artenspace's programs are not well-publicized through its social media accounts. Therefore, community service activities are needed to provide digital marketing training to Artenspace crew. The digital marketing training is designed to last for one month, encompassing research, training, and evaluation phases. This training is intended for Artenspace's social media account manager as the main participant. As a strategic step in training implementation, initial research was conducted by the service team in the first week. Subsequently, training was conducted through offline and online methods. Offline training was delivered through lectures, workshops, and face-to-face discussions in one day, covering content creation training and photography-videography workshops. Online training was conducted for 3 weeks post-offline, covering content production mentoring, copywriting training, and digital marketing research. Meanwhile, evaluation and monitoring were held weekly during online training. The results of digital marketing training for Artenspace crew produced 12 Instagram social media content pieces with a 69% increase in reach. It is hoped that with the improvement in both quality and quantity of Artenspace's social media content, Artenspace programs can better reach a wider target audience and be more effectively communicated to the targeted consumers.